Tarsomere and distal tibial glands: structure and potential roles in termites (Isoptera: Rhinotermitidae, Termitidae) - Costa-Leonardo, Ana Maria [UNESP]; Soares, Helena Xavier [UNESP]; Haifig, Ives; Laranjo, Lara Teixeira [UNESP] (Elsevier B. V., 2015)
Social insects have numerous exocrine glands, but these organs are understudied in termites compared to hymenopterans. The tarsomere and distal tibial glands of the termites Heterotermes tenuis, Coptotermes gestroi and Silvestritermes euamignathus were investigated by scanning and transmission electron microscopy. Pore plates are visible in scanning micrographs on the distal tibial surfaces and on the ventral surface of the first and second tarsomeres of workers of H. tenuis and C. gestroi. In contrast, workers of S. euamignathus have isolated pores spread throughout the ventral surfaces of the first, second, and third tarsomeres and the distal tibia. In all three species each pore corresponds to the opening of a class-3 secretory unit, composed of one secretory and one canal cell. Clusters of class-3 glandular cells are arranged side by side underneath the cuticle. The main characteristics of these exocrine glands include their presence on all the legs and the electron-lucent secretion in the secretory cells. Possible functions of these glands are discussed.
Keywords: Exocrine glands; Legs; Scanning electron microscopy; Social insects; Ultrastructure